(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
Contextual Christian leadership is a crucial need in facing the increasingly complex dynamics of social, cultural, and developmental change. This article aims to examine the integration of Christian faith and local culture as a basis for developing contextual Christian leadership in Christian Religious Education. This research uses a qualitative method with a literature study approach, namely by analyzing various theological sources, Christian education, and relevant cultural studies. The results of the study indicate that Christian faith is essentially contextual and always lived out in specific cultural realities. Local culture plays a significant role in shaping the identity, character, and understanding of the faith of individuals and Christian communities. Christian Religious Education plays a strategic role as a means of developing Christian leadership through the process of internalizing faith values ​​integrated with the local cultural context. The integration of faith and culture enables students to develop a leadership identity that is authentic, reflective, and relevant to the needs of society. Contextual Christian leadership is not only rooted in the teachings of faith but also able to respond to the challenges of the times in a wise and transformative manner.